Effector-Memory γδ T Lymphocytes Predict CMV Disease After the Withdrawal of Prophylaxis in Kidney Transplant Recipients - Yoann Abadie; Jonathan Visentin; Jonathan Visentin; Elodie Wojciechowski; Manon Charrier; Julie Déchanet-Merville; Isabelle Garrigue; Patrick Blanco; Patrick Blanco; Pierre Merville; Pierre Merville; Hannah Kaminski; et al. (Transplant International)
Evaluation of CMV-specific cell-mediated immunity (CMI) has improved strategies to prevent post-transplant CMV disease. This study assessed the association between CMV disease and absolute count of TEMRA γδ T cells at the end of universal prophylaxis in kidney transplant recipients (KTR). We retrospectively analyzed 262 R⁺ and 82 D⁺/R⁻ KTRs who received antiviral prophylaxis and had TEMRA γδ T cells quantified at the end of prophylaxis. The primary endpoint was CMV disease within two years post-transplant. Post-prophylaxis CMV disease occurred in 43/344 (12.5%) patients. A threshold of 4.65/mm³ for TEMRA γδ T-cell count was identified by ROC analysis; higher counts were associated with reduced CMV disease incidence. While no significant association was found in the overall cohort, in R⁺ patients, a count >4.65/mm³ was associated with a 97.7% positive predictive value for protection against CMV disease. Multivariate analysis confirmed its independent association with disease-free survival [HR: 0.27 (95% CI: 0.09–0.85), p = 0.0252]. Measuring TEMRA γδ T-cell counts at the end of prophylaxis may serve as a useful, accessible immune marker to guide CMV prevention strategies in R⁺ kidney transplant recipients.